Construction of Local Isolates of Cyanobacteria for Ethanol Production. - Hasan, Payam Bayazeed; Mohamad, Dlnya Asad (Sulaimani Journal for Pure and Applied Sciences, 2016)
Cyanobacteria can use solar energy and convert carbon dioxide into biofuel molecules in one single biological system. In this research, Synechococcus sp. was isolated from Saray Subhan Agha fresh water, a pure culture of Synechococcus was obtained by several subculturing on BG11 media. For the production of ethanol by Synechococcus sp. pyruvate decarboxylase (PDC) and alcohol dehydrogenseII (ADH II), genes from Zymomonas mobilis ATCC (29191), were amplified by PCR and cloned into the pSyn_1⁄D-TOPO® Vector. The Synechococcus and Synechococcus elongates transformed with constructed vector (pSyn_1⁄D-TOPO®) that harboring the two ethanol fermenting genes. The transformation was performed using a double homologous recombination system to integrate the PDC and ADHII genes into the local isolates of Synechococcus sp. and Synechococcus elongatus chromosome under the control cyanobacterial weak constitutive nickel inducible promoter. The recombinant Synechococcus cells grow in different concentrations of NiSO4 (1, 2.5, 5, 7.5, 10) μM in BG11 media, under different temperature (15, 30, 45) ̊C and different light intensity (10, 50, 150) μE. The enzymatic ethanol assay kit was used to determine ethanol concentration produced by both recombinant Synechococcus sp. and recombinant Synechococcus elongatus. Highest ethanol concentration obtained by those cultures containing five μl NiSO4, which incubated under continues light of 50μE at 30 ̊C (Optimum um condition for ethanol production by recombinant Synechococcus cells). The amount of ethanol produced by local isolates of Synechococcus sp. was 0.00103 g/l, whereas for Synechococcus elongatus was 0.0138 g/l. The amount of ethanol produced by those Synechococcus cultures containing different concentrations of NiSO4 were incubated under continuous light of (10 and 150) μE and temperature of (15 and 45) ̊C was less than those cultures were incubated under light of 50 μE and temperature of 30 ̊C.
Keywords: cyanobacteria,Synechococcus,Ethanol; Sulaimani